SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB MENGGUNAKAN WATERFALL - Ndruru, Melania Dewi Fitriani; Simanjuntak, Taufik Ismail; Siti Agus Kartini (JURNAL WIDYA, 2025)
Libraries have an important role in supporting the teaching and learning process; homever, library management that is still conducted manually often causes several problems, such as difficultes in finding books, inefficient recording of borrowings and returning transaction, and the risk of data loss. This study aims to design and develop a web-based library information system to improve the efficiency, accuracy, and quality of library services at SMK Negeri 1 Amandraya. The system development method used is the Waterfall method, which consists of the stages of requirements analysis, system design, coding, testing, and maintenance. The system was developed using the PHP programming language, a MySQL database, and the Bootstrap 4 framework as the user interface. The results indicate that the developed information system is capable of managing member data, book data, borrowing and returning processes, as well as fine payments managed by administrators. In addition, the system provides an online book feature that can be accessed directly by students. The implementation of this web-based library information system is expected to improve effectiveness, accelerate the borrowing process, and facilitate access to book information for library users. Keywords: Information Systems, Library, Web, Waterfall, PHP